(untitled) (Baghdad Science Journal, 2007)
This research has been applied on 100 children (age 4 – 6 years) from three kindergartens distributed on basis of 43 children from the college of Education for women kindergarten (A) , 27 children from the governmental Al- Mustafa kindergarten (B) , and 30 children from the private Al – Baraom kindergarten (C) . Details concerning their school meals, already prepared at home , have been analyzed according to their dietary components taken from the tables of the dietary values .The statistical analysis results have shown no significant difference (p< 0.01) in the intake of energy , protein and thiamin between the children of A and C kindergartens while these children have significantly recieved higher amounts of the above nutrients from B children . Similar trend of differences (p < 0.05) among the three kindergartens was reported for calcium , niacin , while no significant difference was observed among the three kindergartens in iron , vit . A, riboflavin and ascorbic acid . The comparison between the average intake recieved by the children of A and C kindergartens and the RDA did not show any significant difference from the standpoint of energy , riboflavin and niacin and also between B kindergarten and the RDA from the standpoint of protein ,riboflavin and niacin . However , the intakes of calcium and vit. A of kindergarten A children were significantly less than RDA and significantly more than RDA for protein , iron , thiamin and ascorbic acid , while the intakes of energy , calcium , iron , vit. A and thiamin by kindergarten B were significantly less than RDA and more ascorbic acid . Kindergarten C children , however , recieved significantly less calcium , iron and vit .A and significantly more protein , thiamin and ascorbic acid than RDA . The percentages of children according to the food groups intake were calculated and no significant differences (p < 0.05) were observed in the intakes of bread and cereals group and milk and its products group between A and C kindergartens children , while B children recieved significantly less amounts than A and C children . Concerning meats and eggs , however , significant differences ( p < 0.05 ) were shown between children intakes of the three kindergartens , so that A recieved more amounts then both B and C and C recieved more than B . In regards of fruits and vegetables group , no significant differences ( p < 0.05 ) were reported between the intakes of B and C kindergartens , while A children recieved significantly more amounts than B and C children .